Spinal tumors in children - Joaquim,Andrei Fernandes (2017)
Summary Introduction: Spinal tumors are rare in the pediatric population, presenting many specific peculiarities when compared to adults. We have performed a broad narrative review to describe the most common spinal tumors in children, discussing their main characteristics and management options. Method: The authors have performed an extensive review of the peer-reviewed literature addressing the aforementioned objectives. Results: Multimodality radiological studies (plain films, 3D computed tomography scan and magnetic resonance imaging) are necessary for proper evaluation and differential diagnosis of spinal tumors in children. In selected cases nuclear medicine imaging is used to improve the chances of a more accurate diagnosis. As a general rule, a fine needle biopsy is recommended after radiological evaluation to confirm the tumor's histology. Primary bone tumors can be divided into benign bone tumors, mostly represented by vertebral hemangiomas, osteoid osteomas, osteoblastomas, aneurismal bone cysts, and eosinophilic granulomas, and malign or aggressive tumors, such as Ewing's or osteogenic sarcomas. Secondary bone tumors (spinal metastases) comprise different tumor histologies, and treatment is mainly based on tumor's radiosensitivity. The characteristics and treatment options of the main spinal tumors are discussed in details. Conclusion: Spinal tumors in children are rare lesions that demand a thorough understanding of their main characteristics for their proper management. Understanding the nuances of spinal tumors in children is of paramount importance for improving outcomes and chances of cure.